(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione SOMMARIO: 1. Premessa – 2. Verso una concreta assunzione di responsabilità della Chiesa cattolica in materia ambientale – 3. L’impegno delle Diocesi in materia di tutela ambientale – 4. L’impegno della Chiesa cattolica nella tutela dell’ambiente come espressione del principio di collaborazione con lo Stato per il bene del Paese e per la promozione dell’uomo – 5. La partecipazione degli enti religiosi alla costruzione di una “democrazia ambientale” – 6. Enti religiosi e diritto di accesso alle informazioni ambientali – 7. Enti religiosi e tutela giurisdizionale degli interessi diffusi in materia ambientale – 8. Riflessioni conclusive. Confessioni religiose e accesso alla giustizia ambientale. Religious institutions and environmental protection Abstract The article underlines the importance of religions in the global ecological crisis. It also analyzes all the hidden potential of the religious institutions, that can represent an important and useful actor in the necessary ecological commitment. In fact their contribution for the protection of nature can become a really concrete action according to Aarhus Convention, ratified by Italy in 2001. It’s possible to observe that in Aarhus Convention there are no obstacles to the recognition of an active rule on these religiously inspired institutions. That’s why it becomes necessary to study all the consequences, in order to identify powers and limits of this contribution, according to Italian legal system.